Machine tool spindles. Evaluation of machine tool spindle vibrations by measurements on spindle housing. Gear-driven spindles with rolling bearings operating at speeds between 600 r/min and 12 000 r/min Part 3, (4th March 2020) - British Standards Institution,
No abstract available